Land Use/ Land-Cover changes and their impacts on ecosystem services values: a spatio-temporal analysis in Mila, Algeria from 1994-2024 - Souici, Imane; Zouak, Zakaria (Future Science, 2024)
Monitoring spatio-temporal changes in land use and land cover (LULC) and the value of ecosystem services (ESV) contributes significantly to sustainable development and management. Over the last 30 years, LULC has changed enormously in the Mila region of eastern Algeria, covering approximately 69,052 hectares. The Mila municipality, located on a minor affluent of the Oued Rhumel and dominated by the Marchau mountain, is one of the most crucial functional ecological and environmental zones in the country. Utilizing remote sensing, four satellite images of the study area, dated between 1994 and 2024, were visually interpreted to obtain LULC data classification and global value coefficients, which were then used to evaluate local spatio-temporal changes in ESV and LUC over this period. Five LULC types were identified in the study area: Urban Area, Active Agriculture, Vegetation, Soil (bare land), and Water Body. These classifications were used in conjunction with ecosystem service value coefficients to analyze the changes. The results indicated that from 1994 to 2024, vegetation (shrubs and grasslands) decreased, while built-up land (urban areas), water bodies (due to the construction of the Beni Haroun dam), and cultivated land increased. This study underscores the vital role of the wilaya of Mila in the regional system of maintaining landscape change and provides a scientific reference and cartographic tool for the sustainable development of land resources and ecosystem services in semi-arid regions.